Procalcitonin and clinical factors associated with severe dengue infection in hospitalised adults in Malaysia / Huzairi Sani - Sani, Huzairi (2018)
Background: Dengue infection is the commonest mosquito-borne viral infection that results in hospitalisation amongst patients in Malaysia. The cornerstone of managing dengue infection is the prediction hence prevention of severe dengue from developing. Warning signs proposed by WHO as clinical predictors of severe dengue are insensitive. Procalcitonin (PCT) has been shown to increase in bacterial infections and is useful in predicting disease severity and mortality. Objective: To determine the level of PCT and other clinical and biochemical parameters in inpatient adults with dengue fever. Methods: This is a prospective observational study conducted over 6 months from September 2017 to February 2018. Patients aged 18 years and above who were hospitalised in Hospital Selayang for a serologically-confirmed dengue fever were recruited. PCT level was taken upon recruitment within 24 hours of hospital admission. Patients were followed up throughout admission until discharge or death. Results: Out of 133 recruits, 117 (88%) had uncomplicated dengue and 16 (12%) had severe dengue either with shock (44%) or organ failure (56%). There were 2 (13%) deaths from the severe group. Median PCT levels were higher in severe [0.35 ng/mL (0.15-4.4)] versus non-severe [0.28 ng/mL (0.17-0.54)] dengue, however there was no significant difference between both groups (p=0.518). Other clinical and biochemical factors analysed showed there was significant values for defervescence phase (p=0.043), lethargy (p=0.000) and albumin <35g/L (p=0.015). On multivariate analysis, parameters significantly associated with severe dengue include lethargy (p=0.001) and hypoalbuminemia (p=0.009). These two parameters plus PCT >0.3 ng/mL predict severe dengue with a sensitivity of 73% and specificity of 85%. PCT [median 3.6 ng/mL (3.2-4.0)] is also significantly associated with death (p=0.021). Conclusion: PCT at a cut-off of >0.3 ng/mL predicts severe dengue when combined with lethargy and albumin <35g/L. Furthermore, PCT is significantly associated with death.